Manufacture of super large tungsten single crystals in the form of rotation bodies - Shapovalov, V.O.; Nikitenko, Yu.O.; Yakusha, V.V.; Gnizdylo, O.M.; Sheiko, I.V. (Вопросы атомной науки и техники, 2020)
The results of researches made at creation of technology of production of super-large single crystals of tungsten in the form of plates and bodies of rotation are presented in E.O. Paton Electric Welding Institute NAS of Ukraine created a unique technology for the production of single crystals of refractory metals in the form of plates 170×160×20 mm, worked out the technology and conducted material studies, which confirmed their quality and gave the basis for further development in this direction. In recent years, the technology of growing super–large single–crystal tungsten in the form of rotating bodies with a diameter of 85 mm has been created. Представлено результати досліджень, проведених при створенні технології отримання супервеликих монокристалів вольфраму у вигляді пластин та тіл обертання. В ІЕЗ ім. Є.О. Патона НАН України була створена унікальна технологія вирощування монокристалів тугоплавких металів у вигляді пластин 170×160×20 мм, відпрацьована технологія та проведені матеріалознавчі дослідження, що підтвердили їхню якість та дали підґрунтя для подальших розробок у цьому напрямку. В останні роки було створено новітню, не маючу світових аналогів, технологію вирощування супервеликих монокристалів вольфраму у вигляді тіл обертання діаметром 85 мм. Представлены результаты исследований, проведенных при создании технологии получения супербольших монокристаллов вольфрама в виде пластин и тел вращения. В ИЭС им. Е.О. Патона НАН Украины была создана уникальная технология выращивания монокристаллов тугоплавких металлов в виде пластин 170×160×20 мм, отработана технология и проведены материаловедческие исследования, которые подтвердили их качество и создали основу для дальнейших разработок в этом направлении. В последние годы было создано новую не имеющую мировых аналогов технологию выращивания супербольших монокристаллов вольфрама в виде тел вращения диаметром 85 мм.